First in vivo visualization of MRI‐visible IPOM in a rabbit model. Issue 6 (28th January 2014) - Otto, Jens; Kuehnert, Nicolas; Kraemer, Nils A.; Ciritsis, Alexander; Hansen, Nienke Lynn; Kuhl, Christiane; Busch, Daniel; Peter Neumann, Ulf; Klinge, Uwe; Conze, Klaus‐Joachim
Abstract Background: Application of a mesh in presence of pneumoperitoneum may cause deformation or wave formation when gas is released. Moreover, mesh shrinkage during subsequent wound healing cannot be detected in vivo without invasive diagnostics. Using MRI‐visible polyvinylidene fluoride (PVDF) mesh, the extend of mesh deformation and shrinkage could be objectified by MRI for the first time. Materials and Methods: Laparoscopic intraperitoneal onlay mesh (IPOM) implantation was performed in 10 female rabbits using ferro‐oxide loaded PVDF meshes. MRI measurements were performed postoperatively at days 1 and 90. After three‐dimensional reconstruction of all MRI images the total surface and the effective surface of the implanted mesh were explored and calculated computer‐assisted. Results: In all cases, the mesh could be identified in MRI. The subsequent three‐dimensional reconstruction always allowed a calculation of the mesh area. In relation to the original size of the used textile implant, we found neither a significant reduction of the effective mesh surface after release of the pneumoperitoneum at day 1 after laparoscopic surgery nor a significant change of the total surface of this large pore mesh by the end of the observation period. Conclusions: In vivo investigation of mesh surface via MRI could exclude a significant initial reduction of the effective mesh surface after release of pneumoperitoneum, in this IPOM rabbit model. A further subsequent shrinkage of these large pore PVDF meshes could be excluded, as well. Imaging of MRI‐visible IPOM mesh turned out to be a sufficient tool to objectify mesh configuration and position in vivo. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 1165–1169, 2014.